Clinical features of patients with chronic liver disease in Japan related to alcohol use: Nationwide examination using alcohol use disorders identification test. Issue 1 (15th September 2022) - Hiraoka, Atsushi; Nakai, Masato; Hara, Nagisa; Hanai, Tatsunori; Namisaki, Tadashi; Miyaaki, Hisamitsu; Nakahara, Takashi; Hiramatsu, Akira; Ohama, Hideko; Tada, Fujimasa; Takahashi, Hirokazu; Aikata, Hiroshi; et al.
Abstract: Aim: Patients often do not respond truthfully to physicians' interviews concerning alcohol. Few reports regarding the level of alcohol dependence in patients with chronic liver disease (CLD) have been presented. This study aimed to elucidate severity distribution in patients with CLD using the alcohol use disorders identification test (AUDIT). Methods: From March to June 2022, 2034 Japanese outpatients with CLD, including 415 cases associated with hepatitis C virus, 436 with hepatitis B virus, 173 with alcohol‐related liver disease (ARLD), and 1010 with other factors, were interviewed using AUDIT. Clinical features related to alcohol use in these patients were then retrospectively evaluated. Results: In all patients, an AUDIT score 8–14 (harmful use) was noted in 5.8% of hepatitis C virus, 8.9% of hepatitis B virus, 24.3% of ARLD, and 4.4% of other groups, respectively ( P < 0.001), while a score ≥15 (dependency) was noted in 3.4%, 3.0%, 27.7%, and 1.9%, respectively ( P < 0.001). When the country was divided into regions, the percentages remained similar. Comparisons between patients with and without an AUDIT score ≥8 ( n = 1412), performed after exclusion of those without related data ( n = 622), showed no significant differences for hepatic reserve function, while those with harmful alcohol use were significantly younger (66 vs. 70 years, P = 0.006) and had a larger percentage of men (80.4% vs. 45.1%, P < 0.001). Conclusion: Harmful alcohol and alcohol dependency were observed in approximately 10% of patients with viral or non‐viral CLD, after excluding patients with ARLD. Assessment of alcohol intake by use of the AUDIT questionnaire as well as adequate intervention should be considered necessary.